0537 Positive Effects of Long Term Continuous Positive Airway Pressure (CPAP) Therapy on Blood Pressure in Obstructive Sleep Apnea Patients. (12th April 2019) - Shirahama, Ryutaro; Tomooka, Kiyohide; Yun, Lan Fan; Ikeda, Ai; Endo, Tomoki; Wada, Hiroo; Kales, Stefanos N; Tanigawa, Takeshi
Abstract: Introduction: OSA is one of the common causes of secondary hypertension. It leads to nocturnal and early morning hypertension and increased blood pressure fluctuation; these are the risks for cerebrovascular events. To investigate longitudinal effect of continuous positive airway pressure (CPAP) therapy and its adherence on blood pressure reduction in obstructive sleep apnea (OSA) and the relation between CPAP therapy and body weight change. Methods: One thousand two hundred ninety-three (male 1, 130, female 163) patients, who were diagnosed with OSA and underwent CPAP therapy, were investigated for longitudinal changes in blood pressure and body weight. Analysis of covariance was applied for comparison of mean values. Multiple linear regression analysis was performed to assess linear relations between continuous dependent variables. Logistic regression analysis was performed to assess binary dependent variables. MICE (Multiple Imputation with Chained Equations) was used to impute missing data. Results: The patient group with good CPAP adherence (usage rate of CPAP ≧70% over 4 hours) showed significant blood pressure reduction compared to the poor CPAP adherence group (usage rate of CPAP < 70% over 4 hours) at 24 months observation period (p<0.01) . The poor adherence group tended to increase body weight, whereas the good CPAP adherence group showed less increase in body weight at 24 months observation periods. For age70 subgroup, good CPAP adherence group showed significant decrease of diastolic blood pressure at 24 months observation period (p=0.035). Conclusion: CPAP therapy had a significant blood pressure reduction effect in OSA patients. CPAP adherence may effect on greater blood pressure reduction preventing body weight gain. Support (If Any)